Some Aspects of Pediatric Intensive Care Unit - Rusepno Hassan; Y.A. Kasim (Indonesian Pediatric Society, 1980)
A pediatric intensive care unit is a matter of fact indispensable for a pediatric hospital. The Pediatric Department of the Dr. Cipto Mangunkusumo General Hospital, although not really a pediatric hospital, has a capacity of 300 beds for infants and young children; therefore, it is only natural that the department should acquire its own intensive care unit. On July 1, 1976, we established the Intensive Care Unit, furnished at first with simple equipments, and eventually with more modern ones. In the first ten months of operation we were able to treat 154 cases with a mortality rate of 51.9%. This high rate is mainly due to the severity of the cases treated and the delay of hospitalization.